Growth of Pancreas and Intestinal Enzyme Activities in Growing Goats: Influence of a Low-Protein Diet - Kefyalew Gebeyew (MDPI AG, 2021)
A dependence between dietary protein and starch levels flowing to the duodenum has been characterized in monogastric animals for optimal enzymatic secretions of the pancreas, but those in ruminants remain unclarified. The present experiment was conveyed to assess the pancreas growth and mRNA expression of the small intestine enzymes in growing goats fed a low-protein diet. Twenty-four Liuyang goats (19.55 ± 3.55 of body weight (BW)) and aged approximately 8 months were randomly assigned to either a control protein diet (NP: 10.77% CP) or a low-protein diet (LP: 5.52% CP) for 70 days. The results show that no statistical differences (p > 0.05) were observed in the pancreas growth indices between the groups. Pancreas and small intestine α-amylase and lipase activities were unaffected (p > 0.05) by the LP diet, while activities of trypsin and chymotrypsin were decreased (p < 0.05). The LP diet reduced (p < 0.05) the mRNA expressions of trypsin and chymotrypsin in the duodenum and jejunum, and had no effects (p > 0.05) on the mRNA expressions of α-amylase and lipase. Goats fed with the LP diet had higher (p < 0.05) concentrations of cholecystokinin and insulin than those fed with the NP diet. In conclusion, feeding an LP diet (5.52% CP) had no profound influence on pancreas growth and digestive enzyme synthesis in goats.